Committee on Essential Commodities and Articles of Mass Consumption Report - Planning Commission (Planning Commission, 1973)
In order to ensure the success of the distribution system, severe and harsh action must be taken against hoarders, blackrarketeers and all these who try to flout the system. Involvement of local citizens, particularly youngsters for proper vigilance, right from procurement to distribution is very essential and should be secured through advisory committees.
Planning Commission Government of India
Planning Commission Government of India